PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium cepa L.) VARIETAS BREBES AKIBAT PEMBERIAN PUPUK ORGANIK CAIR - Kantikowati, Endang; Karya; Murti Minangsih, Dian; Nugroho Salam, Ibnu (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2023)
This study aims to determine the concentration dose of liquid organic fertilizer, as well as to obtain the concentration that can have the best effect on the growth and yield of shallots (Allium cepa L.) Brebes variety. The study was conducted in Cibiana Village, Cikalong Village, Cimaung District, Bandung Regency , West Java Province, with an altitude of 995 m above sea level, with rainfall of 2,354.2 mm/year including type C2 rainfall according to Oldeman (1975), with a pH of 6.67 (neutral). This study used a randomized block design (RBD) method, which consisted of six treatments with four replications. The concentration treatment of liquid organic fertilizer is as follows: A (0 without fertilizer), B (2 ml/l), C (4 ml/l), D (6 ml/l), E (8 ml/l) and F ( 10ml/litre). Testing the difference between the two means was carried out using Duncans' multiple range test at the 5% level. The results showed that the application of liquid organic fertilizer at a concentration of 10 ml/l had a better effect on plant height and tuber weight.